(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. Diabetic nephropathy is a major cause of morbidity and mortality among young adults with type 1 diabetes mellitus (DM). Albuminuria, the gold standard for early diagnosis, cannot always detect early diabetic nephropathy. We aimed at evaluating the level of urine neutrophil gelatinase-associated lipocalin (NGAL) as a marker of tubulointerstitial damage in children and adolescents with type 1 DM in relation to the level of albuminuria and other parameters. Materials and Methods. Fifty children with type 1 DM for more than 5 years were included in this study (mean age, 13.8 ± 4.0 years), and 18 healthy children served as controls. Patients with overt albuminuria (> 300 mg/g creatinine) or inflammatory states were excluded. Urine NGAL, microalbuminuria, and urine albumin-creatinine ratio were measured in patients and controls as well as other parameters. Results. Urine NGAL was significantly higher in microalbuminuric in comparison with normoalbuminuric patients and controls, and correlated positively with urine albumin-creatinine ratio. A positive urine NGAL was observed in 12 of 38 normoalbuminuric patients (31.6%) compared to 9 of 12 microalbuminuric patients (75%). A positive correlation was reported between urine NGAL and both Hemoglobin A1c and duration of DM, but not with estimated glomerular filtration rate or hypertension. Conclusions. Diabetic children, even some normoalbuminurics, showed increased urine NGAL. This finding may support the hypothesis of a "tubular phase" of diabetic disease preceding overt diabetic nephropathy, and hence, the use of urine NGAL measurement for early evaluation of renal involvement.